2015
DOI: 10.3109/1354750x.2015.1045032
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum periostin is associated with liver stiffness and clinical outcome in biliary atresia

Abstract: Serum periostin was associated with liver stiffness in BA. Thus, serum periostin has potential as a parameter reflecting the severity in BA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
4
4
0
Order By: Relevance
“…These findings may suggest that periostin is rapidly secreted into the bile, so periostin immunostaining is only seen when the bile flow is disturbed. Consistent with this idea, the serum 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 level of periostin in patients with biliary atresia was significantly higher than control [42]. In addition, immunostaining of liver sections from patients with non-cholestatic liver cirrhosis has not detected periostin in either hepatocytes or fibrous hepatic stroma [42,43].…”
Section: Deletion Of Periostin In Mice Attenuates Liver Fibrosis Caussupporting
confidence: 58%
“…These findings may suggest that periostin is rapidly secreted into the bile, so periostin immunostaining is only seen when the bile flow is disturbed. Consistent with this idea, the serum 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 level of periostin in patients with biliary atresia was significantly higher than control [42]. In addition, immunostaining of liver sections from patients with non-cholestatic liver cirrhosis has not detected periostin in either hepatocytes or fibrous hepatic stroma [42,43].…”
Section: Deletion Of Periostin In Mice Attenuates Liver Fibrosis Caussupporting
confidence: 58%
“…Recent studies by Popov et al (18) and others (38)(39)(40) indicate that the LOX inhibitor β-aminopropionitrile (BAPN) may provoke hepatic progenitors to replace the ductular reaction associated with portal fibrosis; hence, there is a strong rationale to investigate additonal targets mediating collagen cross-linking in fibrosis injury. These studies are collectively corroborated by recent human studies indicating children who suffer from biliary atresia (BA) have significantly higher circulating levels of periostin (41). Indeed, periostin as a marker for fibrotic injury has long been a surrogate for lung fibrosis (42).…”
Section: Discussionsupporting
confidence: 73%
“…This previous study concluded that serum PN was associated with hepatic dysfunction, liver fibrosis and jaundice status (50). The univariate analysis conducted in the present study demonstrated that serum PN was significantly associated with PT.…”
Section: Discussionmentioning
confidence: 97%
“…Serum PN is positively associated with liver enzymes and proteins (aspartate transaminase, alanine transaminase, alkaline phosphatase and total albumin) and liver stiffness, but negatively associated with serum albumin in patients with post-operative biliary atresia (50). This previous study concluded that serum PN was associated with hepatic dysfunction, liver fibrosis and jaundice status (50).…”
Section: Discussionmentioning
confidence: 99%